Decolonisation from the Margins: Shack Theatres and the Experience of the Khayelitsha Art School & Rehabilitation Centre (KASI RC) in South Africa - (:unkn) unknown (My University, 2025)
The issue of decolonisation of the arts and education is at the centre of many intellectual debates and controversies around the world, and particularly in South Africa. In Khayelitsha, the largest township in Cape Town, Mandisi and Liso Sindo have chosen to concretely address the power structures and cultural hierarchies that were imposed by colonisation and apartheid and that continue to exclude black people, by creating a “shack theatre” that allows inhabitants to express themselves, to access their creativity and produce works and performances. Established in 2017, the Khayelitsha Art School & Rehabilitation Center (KASI RC) constitutes an original experience where the question of the decolonisation of arts and knowledge is posed in a concrete way and as close as possible to those who are concerned by the violence, oppression and more generally the contempt of the (post)colonial society. Based on a joint reflection engaged from 2019 between the main initiator of this shack theatre, Mandisi Sindo, and two French sociology researchers, this article’s aim is to produce an ethnographic analysis of the conditions of realisation of the KASI RC project. We thus identify three main orientations: conscientisation, participation and requalification, which contribute to make KASI RC and shack theatres quite singular initiatives in the South African cultural landscape, and even beyond.
Keywords: African Research